Melatonin improves learning and memory performances impaired by hyperhomocysteinemia in rats - Baydas, G; Özer, M; Yasar, A; Tuzcu, M; Koz, ST (Elsevier, 2005)
Oxidative stress has been proposed as a possible mechanism underlying many neurodegenerative diseases associated with hyperhomocysteinemia. In the present study, we investigated the possible link between oxidative stress, expression of neural cell adhesion molecules and spatial learning deficits induced by chronic hyperhomocysteinemia. Furthermore, the effectiveness of antioxidant melatonin against homocysteine neurotoxicity was also examined. Male Wistar rats were treated with either saline or methionine to induce hyperhomocysteinemia and half of methionine-treated rats administered daily melatonin in a dose of 10 mg/kg. We observed that chronic administration of melatonin significantly reduced the lipid peroxidation and restored the decreased glutathione levels induced by chronic hyperhomocysteinemia. Chronic hyperhomocysteinemia significantly impaired learning and memory performance in the passive avoidance test and Morris water maze task. We also found that these cognitive deficits were reversed by chronic treatment with antioxidant melatonin. Furthermore, melatonin administration was able to modulate the expression pattern of neural cell adhesion molecules in hippocampus. The results provide evidence that homocysteine induces long-lasting behavioral deficits, which are possibly caused by oxygen reactive species generation, and by changing in synaptic plasticity and also suggest that melatonin treatment has the ability to prevent nervous system against homocysteine toxicity. (c) 2005 Elsevier B.V All rights reserved.
Keywords: melatonin; homocysteine; NCAM; learning; memory; lipid peroxidation